Escaping Populism – Safeguarding Minority Rights: Non‐majoritarian Dynamics in European Policy‐making*. (26th November 2017) - Thielemann, Eiko; Zaun, Natascha
Abstract: Contrary to earlier predictions, communitarization in the area of asylum policies has not led to an erosion of refugee rights. Instead, there is growing evidence that EU asylum harmonization has safeguarded existing standards and even enhanced the rights of asylum‐seekers and refugees in Europe. We seek to explain this by building on the insights of principal‐agent theory. We argue that delegation to supranational institutions can strengthen non‐majoritarian policy dynamics and shield EU policy‐makers from populist pressures for further immigration restrictions that national governments are often confronted with. We support this argument empirically through a systematic longitudinal analysis of the evolution of EU asylum policies. In particular, we seek to assess the motivation for and impact of greater delegation to EU institutions on rights developments for asylum‐seekers and refugees. We also explain to what extent EU policy‐making has changed with the EU's response to the 'Syrian refugee crisis'.